Advertising Mental Healthcare through Metaverse: Consequential Effects on Stigmatizing Beliefs, Psychological Safety, and Mental Health Literacy - Shahzad Alam Khan, Qurrat-Ul-Ain Fatima, Kashifa Ansari, Mehboob Ahmad, Ahsanullah M Mirbahar, Sohail Safdar (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: to measure the influence of metaverse advertising on mental health literacy and metaverse technology adoption while considering its benefits in complex social and psychological considerations Study Design: Retrospective observational study Place and duration: The data was collected from the department of general medicine Nishtar hospital, Multan in population of Multan from April 2021 to March 2022. Methodology: Our sample size was selected as 400 respondents, considering the confidence interval of 95%, wherein at least 383 respondents are necessary with large population size. In this study, the quantitative data was collected through a self-administered questionnaire and it was prepared on the five-point Likert scale to collect the data from the respondents. Only 392 questionnaires were included in the analysis of the study. On the other hand, the structural model was assessed by calculating beta value, standard deviation, T test and p-values. The significance of any relationship is assessed through p values which should be less than 0.05. Results: The results also confirmed that mental health literacy is improved through metaverse advertising on mental health care and by following the mediating role of stigmatized beliefs and psychological safety. Likewise, H2a was tested to reveal that psychological safety mediates the relationship between Metaverse advertising on mental health care and mental health literacy (β= 0.569, t=7.862, p= 0.000). At the same time, H3a was tested to reveal that stigmatized beliefs mediate the relationship between Metaverse advertising on mental health care and mental health literacy (β= 0.0063, t=2.089, p= 0.018). Conclusion: The results of this study conclude that the metaverse is gaining publicity every day, and its application in medical intervention is beneficial and revolutionary. It can root out long-standing social issues like stigmatizing beliefs and psychological safety. In this way, metaverse advertising on mental healthcare is a proven method to enhance mental health literacy which is the desired outcome of this research study. Practical Implication: Current study looked at how mental health literacy and stigma affect people’s perspectives on psychiatric treatments in population of Pakistan. To the best of our knowledge no such study was found in local population so this study will provide local statistics on this topic. Keywords: Metaverse, Stigmatizing Beliefs, Psychological Safety, Mental Health Literacy, and Mental Healthcare.